The α1 adrenoceptors in ventrolateral orbital cortex contribute to the expression of morphine-induced behavioral sensitization in rats. (1st January 2016) - Wei, Lai; Zhu, Yuan-Mei; Zhang, Yu-Xiang; Liang, Feng; Li, Teng; Gao, Hong-Yu; Huo, Fu-Quan; Yan, Chun-Xia
Highlights: The VLO is a novel anatomical substrate mediating morphine-induced behavioral sensitization. Blocking α1 adrenoceptors in the VLO suppressed the expression of morphine-induced behavioral sensitization. Morphine-induced behavioral sensitization may be associated with activated ERK in the VLO. Abstract: The aim of the present study was to investigate the effect of microinjection of benoxathian, selective α1 adrenoceptor antagonist, into the ventrolateral orbital cortex (VLO) on morphine-induced behavioral sensitization and its underlying molecular mechanism in rats. A single morphine treatment protocol was used in establishing the behavioral sensitization model. The effect of bilateral intra-VLO benoxathian injection on locomotor activity was examined and the protein expression levels of α1 adrenoceptors and activation of extracellular signal-regulated kinase (ERK) in the VLO were detected after locomotor test. The results showed that a single injection of morphine could induce behavioral sensitization by a low challenge dosage of morphine after a 7-days drug free period. Benoxathian significantly suppressed the expression but not the development of morphine-induced behavioral sensitization. Morphine treatment significantly elicited ERK phosphorylation and downregulated the expression level of α1 adrenoceptors in the VLO. In addition, intra-VLO benoxathian injection enhanced the expression levels of α1 adrenoceptors and phosphorylated ERK. These results suggest that α1 adrenoceptors in the VLO are involved in regulating the expression of morphine-induced behavioral sensitization. The effect of decreased locomotor activity by blocking α1 adrenoceptors might be associated with activation of ERK in the VLO.